Measuring radiotelescope phased array feed noise and sensitivity - Hayman, D.; Chippendale, A.; Hotan, A.; Shaw, R.; Hay, S.; Bird, T.; Hall, Peter; Esselle, K. (Institute of Electrical and Electronics Engineers Inc., 2014)
Various challenges have arisen in the measurement of phased array feeds for radiotelescopes. We focus here on measuring the equivalent noise temperature and the sensitivity of these feeds. We outline the differences between characterizing phased array feeds compared with traditional single horn feeds and provide results from our experience in developing phased array feeds for the Australian Square Kilometre Array Pathfinder.